2009
DOI: 10.1108/00012530910973785
|View full text |Cite
|
Sign up to set email alerts
|

Scientific publishing: a case study of Libyan scientists

Abstract: PurposeThe paper aims to report on a research project that explores the extent and scope of scientific publishing, communication, and collaboration amongst Libyan scientists.Design/methodology/approachThe paper commences with a literature review on scientific communication and publishing, including a specific focus on such activities in developing countries. A bibliometric analysis of the papers published by scientists in research centres affiliated to Libya's National Centre for Scientific Research was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
(23 reference statements)
0
11
0
Order By: Relevance
“…such as social networks are used to gain new ideas, share research, communicate with other scholars, and publish research ( Kirkup, 2010;Mahmood et al, 2009; Sauer et al., 2005). These findings, as in this study, suggest that these networks are facilitating scholarly communication activities.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…such as social networks are used to gain new ideas, share research, communicate with other scholars, and publish research ( Kirkup, 2010;Mahmood et al, 2009; Sauer et al., 2005). These findings, as in this study, suggest that these networks are facilitating scholarly communication activities.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The speed of change with regard to using modern informal channels in communication practices would increase if these channels had an impact on the promotion process at academic institutions (Gruzd et al, 2011). Recent studies found that modern, informal channels Downloaded by UNIVERSITY OF EXETER At 00:37 04 August 2015 (PT)such as social networks are used to gain new ideas, share research, communicate with other scholars, and publish research ( Kirkup, 2010;Mahmood et al, 2009; Sauer et al., 2005). These findings, as in this study, suggest that these networks are facilitating scholarly communication activities.…”
mentioning
confidence: 99%
“…Informal channels differ from the formal ones in that they allow more interaction between the transmitter of the information and the receiver, which is difficult in formal channels (Russell, 2001). The obvious benefit of informal communication is that it can help to identify a suitable research idea and hypothesis, define the research approach, refine the findings, and put them in the context of other research (Mahmood et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The obvious benefit of informal communication is that it can help to identify a suitable research idea and hypothesis, define the research approach, refine the findings, and put them in the context of other research (Mahmood et al, 2009). Amidst a background of new scholarly communication channels, and the huge number of papers that discuss scholarly communication on the social web, it is notable that few researchers have investigated changes in the balance of approaches used in scholarly communication.…”
mentioning
confidence: 99%
“…Establishing international collaboration as well as university-industry collaboration is becoming more important for academic research. The structural analysis method applied in this study provides guidance to countries, particularly emerging economies in the Asia-Pacific region, Eastern Europe and Sub-Saharan Africa as well as some countries in the Middle East (Ocholla et al, 2012;Davarpana and Behrouzfar, 2009;Mahmood et al, 2009). These countries are also in the process of developing competitive scientific research systems.…”
Section: Research Collaboration In Malaysiamentioning
confidence: 99%